2011
DOI: 10.1103/physrevb.83.041405
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Landau level spectrum and its density dependence in graphene

Abstract: Scanning tunneling microscopy and spectroscopy in magnetic field was used to study Landau quantization in graphene and its dependence on charge carrier density. Measurements were carried out on exfoliated graphene samples deposited on a chlorinated SiO 2 thermal oxide which allowed observing the Landau level sequences characteristic of single layer graphene while tuning the density through the Si backgate. Upon changing the carrier density we find abrupt jumps in the Fermi level after each Landau level is fill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
122
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 26 publications
12
122
1
Order By: Relevance
“…Figure 4b shows a well-resolved dI /dV spectrum (acquired over the sites indicated in the in situ STM image, Fig. 4a) with a distinctive line shape resembling the energy spectrum of graphene, similar to previous STS observations of graphene on non-metallic substrates [51][52][53] . The minimum in each of the directly measured spectral curves corresponds to the charge-neutral Dirac point (E D ) located at positive bias energy slightly above the Fermi level.…”
Section: Atom-scale Analysis Of Graphene In Silicone Oilsupporting
confidence: 83%
“…Figure 4b shows a well-resolved dI /dV spectrum (acquired over the sites indicated in the in situ STM image, Fig. 4a) with a distinctive line shape resembling the energy spectrum of graphene, similar to previous STS observations of graphene on non-metallic substrates [51][52][53] . The minimum in each of the directly measured spectral curves corresponds to the charge-neutral Dirac point (E D ) located at positive bias energy slightly above the Fermi level.…”
Section: Atom-scale Analysis Of Graphene In Silicone Oilsupporting
confidence: 83%
“…Xue et al also observed the signi cantly reduced charge inhomogeneities in graphene/BN by STM/STS [165]. Due to the improved electronic quality of graphene on BN, the fractional quantum Hall e ect [170], unconventional quantum Hall effect in tri-layer graphene [171] and ballistic transport at room temperature [172] The Landau level quantization was observed for graphene on SiO in STM and STS measurements in a magnetic eld [72,163]. Compared to graphene on conductive substrates, graphene on insulating SiO is convenient for controlling the charge carrier density in graphene with a back gate, and thus the dependence of Landau quantization on the charge carrier density can be measured.…”
Section: Graphene On Silicon Carbidementioning
confidence: 93%
“…High resolution STM images have been achieved for graphene on SiO [56,[161][162][163][164][165] as well as on BN [57,165]. The measured root-mean-square (RMS) surface roughness of graphene/SiO is 1.5 -5.0 Å (∼ 1.5 Å, 60 nm ×60 nm [56]; ∼ 1.5 Å, 30 nm ×30 nm [58]; ∼ 1.9 Å, 250 nm ×200 nm [161]; ∼ 5.0 Å, 10 nm ×10 nm [162]; ∼ 3.5 Å, 195 nm ×178 nm [164]; ∼ 2.2 Å, 100 nm ×100 nm [165]).…”
Section: Graphene On Silicon Carbidementioning
confidence: 99%
See 2 more Smart Citations